(untitled) (Eurasian Journal of Ecology, 2016)
The Immunogenic activity of the first Kazakhstani vector vaccine against brucellosis was studied on guinea pig model. As the vector the recombinant influenza virus serotypes H5N1, H1N1, with Brucellosis inserts OMP 16 , L7L12 were used. A series of experiments on guinea pigs proved highly immunogenic activity of the vector vaccine against brucellosis. The results indicate the importance of cellular immune response to administered antibrucellar vaccine and not humoral as it was previously assumed. Antibody ( humoral immune response ) in brucella antigens appear in the blood of animals usually in response to infection and in response to the introduction of vaccines made from bacterial strains V.abortus . The study proved that developed in RI BSP vector vaccine against brucellosis does not cause the production of antibodies in the animal. The cellular and humoral activity of immunity was determined. A comparative analysis based on the infection index and immunogenicity of the brucellosis vaccine and the first developed antibrucellar influenza vector vaccine was conducted.